Outcomes in young adults with acute ischemic stroke undergoing endovascular thrombectomy: A real‐world multicenter experience. (25th May 2021) - Yeo, Leonard Leong‐Litt; Chen, Vanessa Hui En; Leow, Aloysius Sheng‐Ting; Meyer, Lukas; Fiehler, Jens; Tu, Tian‐Ming; Tham, Carol Huilian; Sia, Ching‐Hui; Jamous, Ala; Behme, Daniel; Kastrup, Andreas; Papanagiotou, Panagiotis; et al.
Abstract: Endovascular thrombectomy (EVT) is the standard of care for anterior circulation acute ischemic stroke (AIS) with large vessel occlusion (LVO). Young patients with AIS‐LVO have distinctly different underlying stroke mechanisms and etiologies. Much is unknown about the safety and efficacy of EVT in this population of young AIS‐LVO patients. All consecutive AIS‐LVO patients aged 50 years and below were included in this multicenter cohort study. The primary outcome measured was functional recovery at 90 days, with modified Rankin Scale of 0–2 deemed as good functional outcome. A total of 275 AIS‐LVO patients that underwent EVT from 10 tertiary centers in Germany, Sweden, Singapore, and Taiwan were included. Successful reperfusion was achieved in 85.1% (234/275). Good functional outcomes were achieved in 66.0% (182/275). Arterial dissection was the most prevalent stroke etiology (42/195, 21.5%). National Institutes of Health Stroke Scale (NIHSS) score at presentation was inversely related to good functional outcomes (aOR: 0.92, 95% CI: 0.88–0.96 per point increase, p < 0.001). Successful reperfusion (aOR: 3.22, 95% CI: 1.44–7.21, p = 0.005), higher ASPECTS (aOR: 1.21, 95% CI: 1.01–1.44, p = 0.036), and bridging intravenous thrombolysis (aOR: 2.37, 95% CI: 1.29–4.34, p = 0.005) independently predicted good functional outcomes. Successful reperfusion was inversely associated with in‐hospital mortality (aOR: 0.14, 95% CI: 0.03–0.57, p = 0.006). History of hypertension strongly predicted in‐hospital mortality (aOR: 4.59, 95% CI: 1.10–19.13, p = 0.036). While differences in functional outcomes exist across varying stroke aetiologies, high rates of successful reperfusion and good outcomes are generally achieved in young AIS‐LVO patients undergoing EVT. Abstract :